Development and Validation of an HPTLC Densitometric Method for Assay of Griseofulvin in Tablets (The East and Central African Journal of Pharmaceutical Sciences, 2018)
A new HPTLC densitometric method for the assay of griseofulvin tablets was developed and validated according to ICH guidelines and USP specifications. The method was developed using a mobile phase prepared with an environmentally friendly solvent system, diethyl ether: toluene (4:1) on pre-coated TLC silica gel 60F254 glass plates with a saturation time of 25 min. Development time of 10 min was required for a migration distance of 70 mm. The best detection wavelength was 299 nm. The Rf value was 0.22 and there were no interferences from the excipients or solvents. With regard to repeatability and intermediate precision, the RSD values were 1.43 and 1.58, respectively. Linearity testing gave the polynomial R2 values, calculated on three consecutive days, of 0.9910, 0.9801 and 0.9840, respectively. The accuracy values tested at 80 %, 100 % and 120 % concentrations were between 98.11-102.66 %. The developed HPTLC densitometric method for the assay of griseofulvin tablets is simple, selective, accurate, reproducible, high throughput, cost-effective and environmentally friendly.
Keywords: High Performance Thin Layer Chromatography (HPTLC); griseofulvin; densitometry; validation